Continuity and change in the ceramic technology of the northwest of Mendoza province (Argentina) - Frigolé Guerra, Cecilia; Durán, Victor; Marsh, Erik; Cortegoso, Valeria (Arqueología, 2023)
In this paper, we present the results of the analysis of a ceramic assemblage from sites located in different altitudinal environments of northwestern Mendoza, with a chronological framework that includes all of the so-called Middle period of the Agropottery stage of Central Western Argentina. To assess the changes and continuities of ceramics within the Middle Period in the study area, and to evaluate the variation between highland and lowland sites, we carried out analyses of different states of measurable and observable attributes at the macroscopic level, taking into account their level of temporal and spatial correlation and co-occurrence. From a synchronous perspective, results suggest few and slight variations between highlands and lowlands, linked to functional requirements of pottery. From a diachronic perspective, we observed changes and continuities in most of the evaluated attribute states. The observed changes do not appear as a break in the archaeological record determined by the presence of allochthonous ceramics but rather as a gradual trend towards the incorporation of certain locally replicated technical choices that co-vary over time, and may be linked to a scenario of changes in subsistence and in population dynamics at the local and regional level.